[SPS seminar on identity - 18 June 2011] - Between the individual and the collective. What historical-cultural context for psychologists? - Gibilisco, Salvatore; Giovannetti, Chiara; Izzo, Paola; Mazzeo, Gabriella; Quaglia, Raffaella; Rastelli, Federica; Reale, Francesca; Sofia, Luigi; Stocchino, Grazia; Terenzi, Valentina (Rivista di Psicologia Clinica, 2011)
This article uses the category of individual/collective to examine the relation between the Italian identity and psychologists’ professional identity. In Italy since the 1970s there has been a gradual emergence of cultures that privilege the individualist aspect. This cultural orientation and the crisis of faith in the institutions and in systems of mediation have led to phenomena of social disintegration and contributed to the spread of anomie and social conformism. An analysis is given of three situations where psychologists deal with the issues considered: the first refers to an intervention of consultancy carried out in a Mental Health Center; the second concerns the psychological intervention in prisons. Lastly, the third case focuses on the dynamics characterising the relation between the professional Order and its members.